THE EFFECT OF IMPLEMENTING GOOD CORPORATE GOVERNANCE, BOARD OF DIRECTOR, AND EARNING PER SHARE TOWARD FINANCIAL PERFORMANCE OF THE COMPANIES WHICH LISTED IN INDONESIA STOCK EXCHANGE AT 2011-2013 - B12111011, Fionne Amelia (Jurnal Manajemen Update, 2015)
This study aims at providing evidence of whether or not the good corporate governance and performance indicators of the public companies which listed at Indonesian Stock Exchange (IDX) are affected by variables that were proposed. The study sample consists of (45) Indonesian public companies which listed at Indonesian stock exchange (IDX) and Indonesian Institute for Corporate Governance. The multiple regression analysis was used to find out whether there is an effect of the corporate governance variables on company’s performance. The result of study revealed that a negative but significant effect exists between corporate governance perception index and the financial performance of these companies –measured by return on equity (ROE) but a negative and insignificant effect exists between corporate governance perception index and Tobin’s q. While, a positive and significant effect exists between board of directors and performance of the sampled companies-measured by return on equity and a positive but insignificant was also observed between board of directors and Tobin’s q. A positive but insignificant relationship is observed between earning per share and performance of the sampled companies-measured either by return on equity (ROE) or Tobin’s q (Q).   Keywords: Board of directors, corporate governance perception index, earning per share, Indonesian Institute for Corporate Governance, Return on Equity, and Tobin’s Q.